Cochlear Implantation in Sporadic Vestibular Schwannoma: A Systematic Literature Review - Bartindale, Matthew Robert; Tadokoro, Kent Sean; Kircher, Matthew Lowell (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study was aimed to perform a systematic literature review by examining outcomes in patients with sporadic vestibular schwannoma (VS) undergoing ipsilateral cochlear implant (CI).Data Sources PubMed-NCBI (National Center for Biotechnology Information) and Scopus databases were searched through October 2017.Study Selection Studies reporting auditory outcomes for each patient when a CI was placed with an ipsilateral sporadic VS were included.Main Outcome Measures Demographic variables, VS characteristics, preoperative hearing metrics, duration of deafness, CI type, approach to tumor resection, postoperative auditory outcomes, and postoperative tinnitus outcomes were reported for each eligible patient within studies. Each study was evaluated for quality and bias.Results Fifteen studies and 45 patients met inclusion criteria. Mean speech discrimination score (SDS) improved from 30.0 to 56.4% after CI placement. The majority when reported had an improvement in tinnitus. Preoperative ipsilateral SDS was a negative predictor of postoperative SDS, while neither tumor resection status, tumor location, duration of deafness, ipsilateral pure tone average, nor timing of CI placement had a significant effect on patient outcome.Conclusions Notwithstanding the challenges inherent with surveillance magnetic resonance imaging (MRI) in the setting of a cochlear implant magnet, select sporadic vestibular schwannoma patients can be considered for cochlear implantation.
Keywords: cochlear implant; vestibular schwannoma; acoustic neuroma; hearing outcomes; sporadic vestibular schwannoma